IMPLEMENTASI SISTEM SIARAN BERJARINGAN DI RBTV (Studi kasus tentang Implementasi sistem siaran berjaringan di RBTV tahun 2012 - 2013) - , Harinawati; , Dr.Phil.Ana Nadya Abrar,MES. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
K To survive RBTV cooperate with ompas Tv by implementing a networked broadcast system, Kompas Tv as RBTV as a parent network and network members. In the application of networked broadcast system is related to communication policy so that the application refers to the regulation (regulatory) system networked broadcasting is regulated in Law No. 32 of 2002 and Ministerial communication regulation 43 of 2009, and how the implementation of networked systems in RBTV broadcast in 2012 through 2013? assessed using case study , the method of time series analysis to see priode before signing (MOU), while the signature after signing a cooperation agreement and the partnership agreement at the level of macro, miso and micro. At the macro - level implementation of a networked system broadcast saw social, economic and political, many broadcasters in Jogjakarta but centralized in Jakarta so that the ads are not economically profitable and politically not have the ability to bargain with the ad agency. At the miso -level communication between the executing agency Kompas Tv and permits only limited government, the absence of a clear SOP in the implementation of the task and the inclusion of the personnel in the implementation structure Kompas Tv. At the micro level, the attitude of consistency is not executed with regard to broadcast relays. Implementation